Green bonds in the Nordic countries: features of development and legal regulation - Frolova, Evgenia E. (Journal of the Belarusian State University. Law, 2020)
Climate and energy challenges, which the world economy, politics and society are facing, indicate the need to implement state environmental programs and create a system of sustainable socially responsible investment. The green economy is being introduced and developed worldwide to establish a balance between environmental stability and economic growth, one of the tools of which are green bonds. The Nordic countries were at the origin of the green bond market and today demonstrate some of the best practices for its development by raising the standards of green investment and playing an active role in the international dialogue in this area. The article examines the experience of countries such as Sweden, Finland, Norway, Denmark and Iceland in the development and legal regulation of the institute of green bonds as one of the most advanced and able to be taken as a basis in other European regions.